TEST AGAINST FINANCIAL AND NONFINANCIAL FACTORS FOR BOND RATING - Akhmadi Akhmadi; Ana Susi Mulyani; Inggit Inggit (Jurnal Ekonomi-Qu, 2022)
In this study, bond ratings of non-financial companies listed on the Indonesia StockExchange from 2013 to 2017 are examined in relation to financial and non-financial aspects. Use a sample of 21 companies drawn from the general business community. The methods used for data analysis included descriptive statistics, logistic regression, and partial hypothesis testing. According to the research, the only factors that positively and significantly affect bond ratings are profitability, bond guarantee, and bond age. Cash, firm size, and auditor reputation have a positive but not very substantial impact..